Maternal Indigenous and Artisanal Coastal Nutrition, the SDG Imperative: A Suggested Renaissance of Ethics for Research and Tertiary Education in the Anthropocene Era - Paul D. Watts (International Journal of Nutrition, 2019)
Maternal nutrition is at the core of any principle-centered projection of Sustainable Development Goals. Without the developmental health of newborns – there is no quality future. Specifically, there are situations all around the globe where Indigenous and Artisanal coastal people suffer from maternal malnutrition inadvertently limiting future potentials in many locations that will be most challenged by climate change. Results from research with Artisanal Fisherfolk in the Philippines and analysis of harvest by the Canadian Inuit people are discussed in terms of the ethics of setting national as well as global education and research priorities.
Keywords: Maternal nutrition